Digital Comics Based on Problem Based Learning Materials of Past Kingdom Heritage to Train Students' Critical Thinking Skills - Chamidah, Intan Azizatul; Ahdhianto, Erif; Barus, Yohannes Kurniawan (Universitas Pendidikan Ganesha, 2024)
Lack of innovation in learning science in elementary schools is one of the problems in education because it can cause students to be passive and reduce interest in learning. In addition, it causes low learning outcomes and students' critical thinking skills, especially in the material of the history of past kingdoms. The purpose of the study was to create digital comic learning media based on problem-based learning of the material of the legacy of past kingdoms to train students' critical thinking skills. The research method used was Research and Development (R&D) with the ADDIE development model. Subjects in the study included students and teachers of grade IV, material experts, and media experts. Data collection techniques used were interviews, questionnaires, and tests. Then, the collected data were analyzed in depth both qualitatively and quantitatively. Validity testing was carried out by material and media experts with a score of 4.7. The teacher response questionnaire scored 4.69, and the student response questionnaire got a percentage of 97.45%. The paired sample t-test showed that there was a significant difference before and after the use of digital comics. The effect size test showed that digital comic media had a high effect on the results of students' critical thinking skills, which were observed through learning outcomes. The study's conclusion shows that the use of digital comics on the material of past kingdoms is feasible, practical, and effective to use during the learning process and positively impacts critical thinking skills and student learning outcomes.